A Study of Japan's experience in Cultural Heritage Protection with Local Community Participation - Shimizu, Natsuki; Sugar, Enkhmend (Mongolian Journal of Arts and Culture, 2025)
In this paper, we first report the results of case study of participatory cultural heritage conservation in Shiraoka City, Minami-Alps City, Hida City and Ichinohe Town in Japan. Secondly, based on the results of the case studies, we pointed out three important points for sustainable participatory cultural heritage protection. 1. Developing and implementing programs, methods, and systems suitable for participants, 2. Providing financial support to local governments from the national government, 3. Organizing participants. Additionally, we considered the roles that academia, local governments, and the national governments should play in ensuring the above conditions in Mongolia. From an academic perspective, it is necessary to raise public awareness of the importance of community participation in the protection of cultural heritage. Furthermore, it is also important to collect international experience of participatory cultural heritage protection and conduct theoretical and practical studies to find an approach suitable for Mongolia. Local administration should train cultural heritage officers who have extensive knowledge about local history, culture, and lifestyle, and who can connect residents and the government to promote smooth cooperation. The national government should provide financial support to local areas and opportunities for sharing information on participatory protection of cultural heritage. Орон нутгийн иргэдийн оролцоотой соёлын өвийг хамгаалах талаарх Япон улсын туршлагаас судалсан нь Хураангуй: Энэхүү өгүүлэлд зохиогчид Япон улсын Шираока, Минами-Альпс, Хида, Ичинохэ хотуудад иргэдийн оролцоотой соёлын өвийг хамгаалах талаар хийж гүйцэтгэсэн туршлага судалгааны ажлын тухай танилцуулах болно. Тус судалгааны үр дүнд үндэслэн иргэдийн оролцоотой соёлын өвийг хамгаалахад шаардлагатай гурван хүчин зүйлийг онцлон тэмдэглэж байна. Үүнд: 1. Оролцогчдод тохирсон систем, арга зүй, хөтөлбөрийг боловсруулан хэрэгжүүлэх 2. Төрөөс орон нутагт санхүүгийн дэмжлэг үзүүлэх 3. Оролцогчдоос төрийн бус байгууллага байгуулах. Түүнчлэн, Монгол Улсад дээрх хүчин зүйлсийг хангаж ажиллахад судалгаа шинжилгээ, орон нутгийн засаг захиргаа, төр засгийн хэмжээнд авч хэрэгжүүлэх шаардлагатай арга хэмжээнүүдийг тус тус авч үзсэн юм. Үүнд: - Судалгаа шинжилгээний хувьд иргэдийн оролцоотой соёлын өвийг хадгалж хамгаалах ажлын үр дүн, ач холбогдлыг олон нийтэд сурталчлан таниулж тэдний мэдлэг ойлголтыг дээшлүүлэх, олон улсын туршлагаас судлан мэдээлэл цуглуулж Монгол Улсад нутагшуулах зорилгоор онол ба практикийн судалгаа явуулах; - Орон нутгийн засаг захиргааны хувьд орон нутгийн түүх, соёл, амьдралын хэв маяг зэрэг өргөн цар хүрээнд мэдлэгтэй, засаг захиргаа болон иргэдийг хооронд нь холбож хамтын үйл ажиллагааг жигдрүүлэн ажиллах чадвартай соёлын өвийн мэргэжилтэн сургаж бэлтгэх; - Төр засгийн зүгээс санхүүгийн дэмжлэг үзүүлэх болон мэдээлэл хуваалцах нөхцөл боломжоор ханган ажиллах зэрэг арга хэмжээг онцлон тэмдэглэлээ. Түрхүүр үгс: эко музей, орон нутгийн өв соёл, хамааралтай хүн ам